Generasi Rabbani: Dakwah Melalui Televisi - Maliki, Noval (Tasamuh: Jurnal Studi Islam, 2018)
The obligation of preaching is essential for all the Muslim that is appropriated by the capability and proficiency every Muslim because the meaning of religious preacher generally is every Muslim or Muslim women of Mukallaf, the obligation attaches and does not separate from the mission as the Muslim. Moreover, for special meaning are they taking special proficiency (mutakhassis) in Islam religion recognized as Islamic teacher. Then, in conveying the preaching, the religious preacher wants the preaching material that was message conveyed by the religious preacher to mad’u that includes the truth and kindness for the people that source from al-Quran and Prophet Muhammad (Hadis) covered faith, Islamic law, and behavior with kinds of knowledge that achieved by him. Nevertheless, in conveying the preaching material, a religious preacher must determine the media to be used; it is able in oral, written, portrayal, audio visual and behavior. The awareness will be importance of media of preaching in conveying the preaching material to get the preaching’s goal. So that, many religious teachers have taken advantage the media of television as the facility in distributing the preaching. One of the religious teachers is Jefri al-Bukhori. He introduces as massive message of preaching in Rabbani generation through television. The Rabbani generation is the generation who believes and Islamic theology, and between of those trusting in God, patience, and positive thinking. To get this matter, it is needed the role and active parents and family’s role to be always train, giving guiding and presenting the environment for the children that always full of Islamic condition